Análise funcional da atenção compartilhada em bebês com deficiência visual: uma replicação - Silva, Thalissa Cazarine da (2025)
Joint Attention (JA) is a triadic process essential for child development, involving the coordination of attention between the infant, an adult, and an event or object. Although traditionally associated with behaviors such as eye contact and pointing, this model becomes limited when applied to infants with visual impairments (VI), who may develop alternative forms of social and cognitive engagement. Despite its relevance, there is a scarcity of studies that examine JA from a behavior-analytic perspective, especially in the context of VI. This study aimed to conduct a descriptive functional analysis of the contingencies that support JA in dyads composed of a sighted adult and a child with VI, aged between 10 and 36 months. Interactions were video-recorded in a structured environment using tasks adapted from the Early Social Communication Scales (ESCS). Video logging enabled the identification of discriminative stimuli, dyadic responses, and the consequences that maintained episodes of JA. Results showed that the adult’s Requesting Speech (RS) and Descriptive Speech (DS) functioned as effective discriminative stimuli for evoking JA responses in infants. Additionally, auditory and luminous stimuli significantly increased the frequency of JA episodes, whereas tasks relying solely on distant visual stimuli led to reduced engagement. The physical proximity of the stimulus also favored the occurrence of JA, although the presence of auditory cues proved more decisive in regulating infant responsivity. Another key finding was the predominance of adult-initiated JA attempts (IJA), which were not always followed by infant responses (RJA). This highlights the need for a contingent and temporally contiguous relationship between IJA and RJA to configure a functional episode of joint attention. These findings offer valuable insights for educational and intervention strategies in the field of Special Education, helping professionals and families foster more responsive and functional interactions. It is recommended that future research develop teaching procedures to expand the IJA and RJA repertoires of infants with VI, as well as parental training programs aimed at enhancing caregivers’ sensitivity in mediating access to discriminative stimuli. The results of this study suggest that infants with visual impairments can learn to engage in joint attention, provided that social interactions are designed in accordance with their sensory limitations and developmental potential.